Lessons from Bayh-Dole: reflections on the Intellectual Property Rights from Publicly Financed Research and Development Act - Barratt, A. (Faculty of Law, University of the Free State, 2010)
The Intellectual Property Rights from Publicly Financed Research and Development Act 51 of 2008 promotes patenting and commercialisation of state-funded science. The Act is similar in scope and objective to the American Bayh-Dole Act. This article explores some of the problems created or exacerbated by the Bayh-Dole Act. Traditionally, American innovation was based on a philosophy of open science. Universities conducted basic foundational research which was freely available to others who wanted to commercialise and build on it, or use it for further scientific research. The Bayh-Dole Act changed the model of science to a proprietary model. One of the problems this created was increased patenting of foundational research tools such as genes and cell-lines, which follow-on researchers require for their own research. Sometimes, research has been blocked or impeded by an inability to obtain research licences to patented research on reasonable terms. The Act has also had a negative effect on scientific collaboration and publishing. The article examines whether South Africa’s Intellectual Property Rights from Publicly Financed Research and Development Act has been able to avoid the most serious of the Bayh-Dole pitfalls.

Wet 51 van 2008 bevorder die patentering en kommersialisering van die wetenskap wat met publieke fondse bedryf word. Wat betref sy omvang en oogmerke lyk die Wet soortgelyk aan die Amerikaanse Bayh-Dole Wet. Hierdie bydrae verken sommige van die probleme wat geskep is of versterk word deur die Bayh-Dole Wet. In Amerika is innovering tradisioneel gebaseer op die sogenaamde ‘open science’-filosofie. Die grondliggende navorsing wat by universiteite bedryf is, was vryelik beskikbaar vir diegene wat dit in die handelswese wou gebruik, of daarop wou voortbou, of dit wou gebruik vir verdere wetenskaplike navorsing. Die Bayh-Dole Wet omskep hierdie wetenskaplike model in ’n eiendomsregtelike model. Een van die probleme wat hierdeur veroorsaak is, is die toename in patentering van basiese navorsingsmiddels, soos gene en sel-linies. Navorsers in die navolging vereis sulke middels vir hul eie navorsing. Soms word sulke navorsing belemmer deur die onvermoë van die navorsers om lisensies te verkry om gepatenteerde navorsing op redelike terme te kan gebruik. Die Wet het ook ’n negatiewe impak op wetenskaplike samewerking en publikasie van navorsing gehad. Hierdie bydrae ondersoek of Wet 51 van 2008 die ernstigste van die Bayh-Dole valstrikke vermy.
Keywords: Intellectual Property Rights from Publicly Financed Research and Development Act 51 of 2008; Bayh-Dole Act; America; South Africa; Patents